The classification of serial posets with the non-negative quadratic Tits form being principal - Bondarenko, V.M.; Styopochkina, M.V. (Algebra and Discrete Mathematics, 2019)
Using (introduced by the first author) the method of (min, max)-equivalence, we classify all serial principal posets, i.e. the posets S satisfying the following conditions: (1) the quadratic Tits form qS(z) : Zˢ⁺¹ → Z of S is non-negative; (2) KerqS(z) := {t | qS(t) = 0} is an infinite cyclic group (equivalently, the corank of the symmetric matrix of qS(z) is equal to 1); (3) for any m ∈ N, there is a poset S(m) ⊃ S such that S(m) satisfies (1), (2) and |S(m) \ S| = m